Environmental risk assessment in livestock manure derived biochars. Issue 69 (6th December 2019) - Wang, Andong; Zou, Dongsheng; Zhang, Liqing; Zeng, Xinyi; Wang, Hua; Li, Longcheng; Liu, Fen; Ren, Bo; Xiao, Zhihua
Abstract : Livestock-manure-derived biochar is one of major products obtained from the pyrolysis of livestock manure. This study quantitatively assesses the pollution level and ecological risks associated with heavy metals in livestock manure and the biochar produced by its pyrolysis. Abstract : Livestock-manure-derived biochar is one of major products obtained from the pyrolysis of livestock manure. This study quantitatively assesses the pollution level and ecological risks associated with heavy metals in livestock manure and the biochar produced by its pyrolysis. The geo-accumulation index (GAI) values of heavy metals in livestock manure were significantly decreased ( P < 0.05) and indicated to be at the grade of uncontaminated expected for Zn in pig-manure-derived biochar (PMB, 0.94, 800 °C) via pyrolysis. Therefore, Zn should be paid more attention in PMB. The risk factors ( E r i ) result shows that heavy metals in biochars were significantly decreased ( P < 0.05) with increasing pyrolysis temperature. Potential ecological risk index values revealed that the integrated risks from the heavy metals were significantly decreased ( P < 0.05) after pyrolysis. Similarly, the risk assessment code values indicated that the risks from the heavy metals in livestock-manure-derived biochars were significantly decreased ( P < 0.05) after pyrolysis. In summary, pyrolysis represents an effective treatment method for livestock manure and can provide an effective method to reduce the risks of environmental pollution.